2009 IEEE International Conference on Signal and Image Processing Applications 2009
DOI: 10.1109/icsipa.2009.5478717
|View full text |Cite
|
Sign up to set email alerts
|

Codebook constrained iterative and Parametric Wiener filter speech enhancement

Abstract: In this paper a new iterative method of speech enhancement using Power Spectral Density (PSD) codebooks of clean speech and several types of noise, is proposed. The proposed algorithm estimates the PSDs of speech and noise of unknown nature and, evaluates the input Signal-to-Noise Ratio (SNR) by solving an over-determined set of equations. No Voice Activity Detection (V AD) or other means of noise spectral estimation such as minimum statistics is used. The pre-calculated codebooks are tree structured for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…This is the approach used in our previous research work where, in fact, speech and noise modeling is carried out through classification of their vector quantized PSDs more accurately said Power Spectral Masses (PSMs). Although very good results are obtained using these codebook constrained methods, their long processing time remains an issue [7], [8]. In the algorithm outlined here it is shown that almost the same results can be obtained using mean vectors of the GMM of speech and noise at a much reduced computation time.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…This is the approach used in our previous research work where, in fact, speech and noise modeling is carried out through classification of their vector quantized PSDs more accurately said Power Spectral Masses (PSMs). Although very good results are obtained using these codebook constrained methods, their long processing time remains an issue [7], [8]. In the algorithm outlined here it is shown that almost the same results can be obtained using mean vectors of the GMM of speech and noise at a much reduced computation time.…”
Section: Introductionmentioning
confidence: 57%
“…Our MMSE solution is similar, in essence, to what was reported in [7] and [8] and is based on solving an overdetermined system of equations using GMMs of speech and different noise source candidates. In fact the mean vectors of power spectra models of noise and clean speech are formed as follows: ∑ ∑ (6) in which refers to the frequency bins in the FFT domain and varies from 0 to 256 in our case for each noise source candidate whose mixture model is available.…”
Section: Mmse Solution Using Over-determined System Ofmentioning
confidence: 91%